2015
DOI: 10.1007/978-94-017-9849-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Micro-XRF Applications in Fluvial Sedimentary Environments of Britain and Ireland: Progress and Prospects

Abstract: This chapter considers applications of micro-XRF in fluvial depositional environments and presents case-studies from Britain and Ireland in three key river management areas: flood reconstruction; pollution and provenance mapping; and floodplain sediment dynamics. Although fluvial sediment archives are typically shorter and more fragmented than marine and lake sediment records, they do offer significant palaeoenvironmental potential, not least because of the sensitivity of river systems to environmental change.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Also cores F‐II, F‐III, and S‐II show a distinct pattern of changing morphodynamics, such as the deposition of high magnitude flood layers and an interbedded succession of coarse and fine sediments. The geochemical pattern of Zr/Ti and Zr/Rb log‐ratios supports the interpretation as high magnitude flood deposits, because Rb, Ti, and Zr are associated to different grain‐size fractions (Turner et al, ). In core F‐III these layers date between 2.1 and 2.0 ka cal BP.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also cores F‐II, F‐III, and S‐II show a distinct pattern of changing morphodynamics, such as the deposition of high magnitude flood layers and an interbedded succession of coarse and fine sediments. The geochemical pattern of Zr/Ti and Zr/Rb log‐ratios supports the interpretation as high magnitude flood deposits, because Rb, Ti, and Zr are associated to different grain‐size fractions (Turner et al, ). In core F‐III these layers date between 2.1 and 2.0 ka cal BP.…”
Section: Discussionmentioning
confidence: 53%
“…Sediments in unit V (core F‐I) and in the basal unit of core S‐I are interpreted as low‐energy, lacustrine still water deposits, as indicated by the clayish texture and occasional plant remains; relatively increased values of Fe, Al, Rb, and Ti in the elemental composition of unit V support this interpretation (cf. Cuven, Francus, & Lamoureux, , Loring, , Turner, Jones, Brewer, Macklin, & Rassner, ). The gray color and a distinct Fe‐pattern (Figure ) indicate reducing conditions as present in an oxygen‐poor environment (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Suspected flood couplets (Turner et al, 2015) were observed in the fine-grained facies of all cores with some being linked to clearly observable grain-size changes and organic capping. At least four of these couplets were present in most cores indicating laterally extensive deposition.…”
Section: Sedimentologymentioning
confidence: 94%
“…Floodplain sediments dominated by overbank deposition processes typically comprise of distinctive couplets, consisting of minerogenic sediment and an organic cap (Turner et al, 2015). The organic cap of a flood couplet within floodplain sediments downstream may represent both in-situ autochthonous accumulation and fluvially transported organics eroded from the peatlands, ultimately forming what may appear to be multiple buried soils.…”
Section: Sedimentology and Grain Sizementioning
confidence: 99%
See 1 more Smart Citation